Kegiatan Pengabdian kepada Masyarakat Sosialisasi Gerakan Abate: Berantas Jentik-Jentik Nyamuk untuk Mencegah DBD di Dusun Motor Barat - Dedent Eka Bimmaharyanto S.; Ade Sukma Hamdani; Recta Olivia Umboro; Syamsul Rahmat; Wahyu Saputra Subani; Alung Suci Utami (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Dengue hemorrhagic fever is a disease caused by a virus that is very dangerous because it can cause patients to die in a very short time. Eradicating the Aedes aegypti mosquito is the most important way to eradicate dengue disease, this is done because vaccines to prevent and drugs to eradicate the dengue virus are not yet available. Abate (tempo’s) is one of the groups of pesticides used to kill insects in the larval stage. The goal is to increase public knowledge about the use of abate as a form of dengue prevention. The method carried out in the implementation of community service activities uses the extension method. As a result, the Abate Movement Program has shown positive results in increasing public awareness and knowledge related to dengue prevention. This activity not only provides education, but also encourages real actions in the neighborhood where residents live, such as the use of abate and the implementation of PHBS.